Lipopolysaccharide downregulates the expression of ZO-1 protein through the Akt pathway - Peicen Zou; Fan Yang; Yijun Ding; Di Zhang; Ying Liu; Jinjing Zhang; Dan Wu; Yajuan Wang (BMC Infectious Diseases, 2022)
Abstract Background Neonatal bacterial meningitis is a common neonatal disease with high morbidity, and can cause serious sequelae when left untreated. Escherichia coli is the common pathogen, and its endotoxin, lipopolysaccharide (LPS) can damage the endothelial cells, increasing the permeability of the blood-brain barrier (BBB), leading to intracranial inflammation. However, the specific mechanism of bacterial meningitis induced by LPS damaging BBB remains unclear. In this study, the mouse brain microvascular endothelial (bEND.3) cells were used as a research object to investigate whether LPS damage BBB through the PI3K/Akt pathway. Methods The bEND.3 cells were stimulated with different concentrations of LPS for 12 h, and the expression of tight junction proteins (ZO-1, claudin-5, occludin) was detected using western blotting. The cells were challenged with the same concentration of LPS (1ug/ml) across different timepoints (0, 2 h, 4 h, 6 h, 12 h, 24 h). Expression of TJ proteins and signal pathway molecules (PI3K, p-PI3K, Akt, p-Akt) were detected. The distribution of ZO-1 in bEND.3 cells were detected by immunofluorescence staining. Results A negative correlation is observed between ZO-1 and LPS concentration. Moreover, a reduced expression of ZO-1 was most significant under 1 ug/ml of LPS, and the difference was statistically significant (P < 0.05). Additionally, there is a negative correlation between ZO-1 and LPS stimulation time. Meanwhile, the expression of claudin-5 and occludin did not change significantly with the stimulation of LPS concentration and time. The immunofluorescence assay showed that the amount of ZO-1 on the surface of bEND.3 cells stimulated with LPS was significantly lower than that of the control group. After LPS stimulation, p-Akt protein increased at 2 h and peaked at 4 h. The titer of p-PI3K did not change significantly with time. Conclusion LPS can downregulate the expression of ZO-1; however, its effect on claudin-5 and occludin is minimal. Akt signal pathway may be involved in the regulation of ZO-1 expression induced by LPS in bEND.3 cells.